Correlation of Intravascular Ultrasound and Instantaneous Wave-Free Ratio in Patients With Intermediate Left Main Coronary Artery Disease. (7th June 2021) - El Hajj, Stephanie C.; Toya, Takumi; Warisawa, Takayuki; Nan, John; Lewis, Bradley R.; Cook, Christopher M.; Rajkumar, Christopher; Howard, James P.; Seligman, Henry; Ahmad, Yousif; Doi, Shunichi; Nakajima, Akihiro; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: There is great degree of interobserver variability in the visual angiographic assessment of left main coronary disease (LMCD). Fractional flow reserve and intravascular ultrasound are often used in this setting. The use of instantaneous wave-free ratio (iFR) for evaluation of LMCD has not been well studied. The aim of this study is to evaluate the use of iFR in the assessment of angiographically intermediate LMCD. Methods: This is an international multicenter retrospective observational study of patients who underwent both iFR and intravascular ultrasound evaluation for angiographically intermediate LMCD. An independent core laboratory performed blinded off-line analysis of all intravascular ultrasound data. A minimum lumen area of 6 mm 2 was used as the cutoff for significant disease. Results: One hundred twenty-five patients (mean age, 68.4±9.5 years, 84.8% male) were included in this analysis. Receiver operating curve analysis showed that an iFR of ≤0.89 identified minimum lumen area <6 mm 2 with an area under the curve of 0.77 (77% sensitivity, 66% specificity; P <0.0001). Among the 69 patients without ostial left anterior descending artery or left circumflex artery disease, receiver operating curve analysis showed that an iFR of ≤0.89 identified minimum lumen area <6 mm 2 with an area under the curve of 0.84 (70% sensitivity, 84% specificity; P <0.0001). The correlation was not significantly different when the body surface area was considered. Conclusions: In this study, in patients with intermediate LMCD, iFR of ≤0.89 correlates with intravascular ultrasound minimum lumen area <6 mm 2 regardless of body surface area. The current study supports the use of iFR for the evaluation of intermediate LMCD.